1981
DOI: 10.1177/001872678103401205
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Relationships Between Organizational Commitment and Job Characteristics, Job Satisfaction, Professional Behavior, and Organizational Climate

Abstract: Commitment to the organization is an important behavioral dimension which can be utilized to evaluate employees' strength of attachment. Keeping employees highly committed is important, especially in not-forprofit firms whose salary scales may not be as competitive as industrial firms. Management is concerned with identifying those variables that are related to organizational commitment in order that they may design organizational strategies to maximize commitment levels. Results in a healthcare institution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 19 publications
3
93
0
3
Order By: Relevance
“…Mowday, et al (1979) defined OC as (1) a strong beliefs in and acceptance of organizational goals and values, (2) a willingness to exert considerable efforts on behalf of the organization and (3) a strong desire to remain as a member of the organization. Researchers over the past years have found that OC is positively associated with participation, power, teamwork and professionalism (Welsch & Lan Van, 1981).…”
Section: Organizational Commitment (Oc)mentioning
confidence: 99%
“…Mowday, et al (1979) defined OC as (1) a strong beliefs in and acceptance of organizational goals and values, (2) a willingness to exert considerable efforts on behalf of the organization and (3) a strong desire to remain as a member of the organization. Researchers over the past years have found that OC is positively associated with participation, power, teamwork and professionalism (Welsch & Lan Van, 1981).…”
Section: Organizational Commitment (Oc)mentioning
confidence: 99%
“…Studies designed to ascertain the antecedents of organizational commitment indicate that this form of commitment is a function of personal characteristics (e.g., age, tenure, education, and need for achievement; Steers, 1977, andWelsh &LaVan, 1981) and situational factors related to the job setting (e.g., climate, role conflict, role ambiguity, job and organizational characteristics; Sherman, 1981, andSteers, 1977). The more salient personal factors are those that reflect employees' personal investments in the firm (e.g., preemployment sacrifices to join the organization, pension plans, status and salary levels attributable to seniority).…”
Section: Determinantsmentioning
confidence: 99%
“…Their finding that global virtual work is beneficial for job complexity and through this job satisfaction indicates that working internationally may also have a positive association with organizational commitment, given that organizational commitment has been linked with job complexity (e.g. Pentareddy, & Suganthi, 2015) as well as job satisfaction (Welsch, & LaVan, 1981). We thus assume that working internationally is part of job enrichment and has a positive effect on affective commitment to the organization.…”
Section: Reactions To Changes In Managerial Work Characteristics -Orgmentioning
confidence: 98%